GnRH agonist-only trigger, compared to dual trigger, reduces oocyte retrieval rate in high responders without affecting cumulative live birth rate - Wang, Yu; Yi, Yu-Chiao; Guu, Hwa-Fen; Chen, Ya-Fang; Kung, Hsiao-Fan; Chang, Jui-Chun; Chen, Li-Yu; Chuan, Shih-Ting; Chen, Ming-Jer (Frontiers in Endocrinology, 2024)
This study compared, in high responders undergoing IVF treatment, GnRH agonist-only trigger and dual trigger on oocyte retrieval rate and cumulative live birth rate (LBR). The aim was to determine if the GnRH agonist-only triggers had provided outcomes comparable to dual trigger, while minimizing the risk of ovarian hyperstimulation syndrome (OHSS).A retrospective, matched case-control study was conducted at Taichung Veterans General Hospital, Taiwan, including women who underwent IVF/ICSI between January 1, 2014, and December 31, 2022. Inclusion criteria were: GnRH antagonist protocol and estrogen level >3,000 pg/ml on trigger day. Exclusion criteria were: immune/metabolic diseases, donated oocytes, and mixed stimulation cycles. Propensity score matching was applied to balance age, AMH level, and oocyte number between the GnRH agonist-only and dual trigger groups. Outcomes were analyzed for patients who had complete treatment cycles, focusing on oocyte retrieval rate and cumulative LBR.We analyzed 116 cycles in the agonist-only group, and 232 cycles in the dual trigger group. No intergroup difference was found in their age, BMI, and AMH levels. The dual trigger group had a higher oocyte retrieval rate (93% vs. 80%; p <0.05), while fertilization rates, blastocyst formation rates, and cumulative LBR were comparable. Notably, no OHSS cases had been reported in the GnRH agonistonly group, compared with 7 cases in the dual trigger group. GnRH agonist-only triggers resulted in a lower oocyte retrieval rate compared to dual triggers but did not significantly affect cumulative LBR in high responders. This approach effectively reduces OHSS risk without compromising pregnancy outcomes, making it a preferable option in freeze-all strategies, despite a longer oocyte pick-up duration and a medium cost. GnRH agonist-only trigger, however, may not be suitable for fresh embryo transfers or patients with low serum LH levels on trigger day.